Early and long‐term electroclinical features of patients with epilepsy and PCDH19 mutation. Issue 6 (27th December 2018) - Chemaly, Nicole; Losito, Emma; Pinard, Jean Marc; Gautier, Agnès; Villeneuve, Nathalie; Arbues, Anne Sophie; An, Isabelle; Desguerre, Isabelle; Dulac, Olivier; Chiron, Catherine; Kaminska, Anna; Nabbout, Rima
ABSTRACT: Aims . Protocadherin 19 ( PCDH19) mutations have been identified in epilepsy in females with mental retardation as well as patients with a "Dravet‐like" phenotype. We aimed to elucidate the electroclinical phenotype associated with PCDH19 mutation, which is currently difficult to identify at onset leading to a delay in diagnosis. Methods . We retrospectively reviewed clinical and EEG data for 13 consecutive patients with PCDH19 mutations or deletions diagnosed at our centers from 2009 to 2011, and followed these patients into adolescence and adulthood. Results . We identified a specific temporal sequence of electroclinical manifestations, identified as three main stages. During the first two years of life, previously healthy girls presented with clusters of afebrile focal seizures. Early seizures were recorded on video‐EEG in 10/13 patients, and were focal ( n =8) with temporo‐occipital and frontal onset. Three patients with strictly stereotyped focal seizures underwent a pre‐surgical work‐up. Two patients started with generalized seizures, one presenting with early‐onset atypical absences and the other generalized tonic‐clonic seizures. During the course of the disease, from two to 10 years, seizures became fever‐sensitive and continued to recur in clusters, although these were less frequent. Seizures were mainly described by eyewitnesses as generalized tonic‐clonic, even though three of five seizures, recorded on EEG, showed a focal onset with fast bilateral spread. Atypical absences and fever‐induced tonic‐clonic seizures remained frequent in only one patient until the age of 16 years. No specific treatment or combination appeared to be more effective over another. Various degrees of cognitive or behavioural impairment were reported for all patients, but it was in the second decade that behavioural disturbances prevailed with hetero‐aggressiveness and behaviour associated with frontal lobe abnormalities leading to psychosis in two. Conclusions . Early recognition of the above features should improve early diagnosis and long‐term management of patients with epilepsy and PCDH19 mutations.